HUBUNGAN TEMU MEDIA DENGAN PROMOSI PEMBERIAN ASI DI MEDIA MASSA - Vita Aristyanita; Toto Sudargo; Kuskridho Ambardi (Berita Kedokteran Masyarakat (BKM), 2018)
Media relations with breastfeeding promotion through mass mediaPurposeThis study aimed to evaluate the publication of coverage of media gatherings on promoting breastfeeding in the mass media organized by Wahana Visi Indonesia (WVI).MethodThe experimental study was conducted using primary data from the ongoing event which was the publication data of WVI media coverage.ResultThere was still inappropriate coverage in using the terminology associated with breastfeeding (30%). The main messages on the media gathering agenda have not been widely used as the main theme in liputan (30%). There was a difference in the quality of content coverage between mass media groups that have a target audience of women or families with mass media that have a general target audience in terms of the main theme, but there is no difference statistically from other facets. There was a strong correlation between the content quality of the coverage with the mass media group in terms of the main theme, but there is no difference from another side. ConclusionMedia gathering on breastfeeding topics can attract mass media to publish coverage. Groups of mass media that have a target audience of women or families and mass media that have a common target audience can be involved in breastfeeding promotion.